The Effect of Smart Bed on Pressure Ulcer Prevention among Patients with Stroke in West Java, Indonesia - Taryudi; Lindayani, Linlin; Mutiar, Astri (The Malaysian Journal of Nursing (MJN), 2025)
Background: Stroke is the third leading cause of mortality in Indonesia, significantly contributing to comorbidities and healthcare costs. The integration of the Internet of Things (IoT) in healthcare has the potential to improve patient care by automating patient movement and vital sign monitoring. Objective: This study aims to evaluate the effectiveness of an IoT-enabled smart bed system in preventing pressure ulcers among stroke patients by automating patient repositioning and monitoring key physiological parameters. Methods: A quasi-experimental study was conducted in a private hospital in West Java, Indonesia, involving 30 stroke patients divided into an intervention group (n=15) receiving the smart-bed system and a control group (n=15) receiving conventional care. The Braden Scale was used to assess pressure ulcer risk. Data collection included pre-test, post-test, and follow-up assessments over a one-month intervention period. Repeated Measures ANOVA was used to analyse differences between groups. Results: The intervention group showed significant improvements in sensory perception (+8.23 points, p=0.001, eta=0.31), humidity (+8.76 points, p=0.002, eta=0.28), activity (+9.12 points, p=0.001, eta=0.37), mobilisation (+8.76 points, p=0.002, eta=0.33), nutrition (F=7.66, p=0.001, eta =0.35), and friction (F=8.22, p=0.001, eta=0.30). The control group exhibited no significant changes across these variables. Conclusion: The IoT-enabled smart bed significantly improved factors related to pressure ulcer prevention, reducing the burden on caregivers and healthcare providers. This technology offers a promising solution for enhancing patient care and reducing pressure ulcer incidence among stroke patients.